Pengaruh Strategi Networking dan Motivasi Bisnis Terhadap Pendapatan Omset Penjualan Produk Halal pada Mitra Business Center HNI Cilacap 3 - Indri Kurniawati; Hakim Hakim; Syafi’ah Syafi’ah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of networking strategy and business motivation on the increase in sales turnover of halal products among partners of Business Center HNI Cilacap. Networking strategy refers to the partners’ ability to build and utilize business networks to expand market reach, while business motivation represents internal drives that encourage partners to run and develop their businesses. This research employed a quantitative approach using a survey method. The research population consisted of partners of Business Center HNI Cilacap, with the sampling technique determined through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression analysis. The results indicate that networking strategy and business motivation have a positive and significant effect on the increase in sales turnover of halal products, with a coefficient of determination of 79.4%. These findings suggest that strengthening effective business networks and enhancing business motivation can significantly improve partners’ sales performance. This study is expected to serve as a reference for HNI Business Center partners in formulating business development strategies to sustainably increase halal product sales turnover.